Low-Cost 3D Depth Sensors for Mobile Applications and Control Systems – Accuracy Assessments Using Surveying Techniques - Janos, Daniel; Ortyl, Łukasz; Kuras, Przemysław (Geomatics and Environmental Engineering, 2025)
This article focuses on low-cost LiDAR (light detection and ranging) sensors and 3D depth cameras. Particular attention was paid to their accuracy and compliance with the technical specifications that were provided by their respective manufacturers. The following devices were tested: Stereolabs ZED 2i, Stereolabs ZED, and Intel RealSense D435i depth cameras, and the Intel RealSense L515 LiDAR sensor. An experiment was carried out to measure a geometrically diverse environment (which is typical for in-motion imaging) where both the measurement range and the distortion that is generated by each device’s algorithms on edges, folds, planes, and 3D objects could be evaluated. Depth sensors are often used with excessive confidence as to their geometric reliability. The aim of this work is to assess the actual accuracy of such sensors, which may constitute the ground truth for accuracy losses that could result from the operations of autonomous vehicles. Based on the results, the accuracy information that was provided by the respective manufacturers was difficult to obtain under real conditions. It was found that the low-cost devices could be used in industrial projects, but their operations must take place under certain conditions and settings. It was also necessary to know their capabilities and limitations in order to take full advantage of what they offer.